2014
DOI: 10.1016/j.jneumeth.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automatic quantification of neurite fasciculation in high-density neurite images by the neurite directional distribution analysis (NDDA)

Abstract: Background Bundling of neurite extensions occur during nerve development and regeneration. Understanding the factors that drive neurite bundling is important for designing biomaterials for nerve regeneration toward the innervation target and preventing nociceptive collateral sprouting. High-density neuron cultures including dorsal root ganglia explants are employed for in vitro screening of biomaterials designed to control directional outgrowth. Although some semiautomated image processing methods exist for qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Although literature suggests that FN decreases neurite extension,78 we found that FN‐functionalized silk gels produced cDRG extensions longer than those cultured on substrates functionalized with LN and NT‐3, perhaps due to FN's integrin and growth factor binding sites acting synergistically with NT‐3 ( Figure a). The extent of fasciculation as a function of distance from the explant body was quantified using an orientational distribution function (ODF) that assessed extent of alignment of neurites with a radially aligned vector field 79. We found ECM‐functionalized silk hydrogels exhibited greater fasciculation of neurites as compared to silk hydrogel alone with NT‐3 (Figure 6b,c).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although literature suggests that FN decreases neurite extension,78 we found that FN‐functionalized silk gels produced cDRG extensions longer than those cultured on substrates functionalized with LN and NT‐3, perhaps due to FN's integrin and growth factor binding sites acting synergistically with NT‐3 ( Figure a). The extent of fasciculation as a function of distance from the explant body was quantified using an orientational distribution function (ODF) that assessed extent of alignment of neurites with a radially aligned vector field 79. We found ECM‐functionalized silk hydrogels exhibited greater fasciculation of neurites as compared to silk hydrogel alone with NT‐3 (Figure 6b,c).…”
Section: Resultsmentioning
confidence: 96%
“…Neurite Directional Distribution Analysis in Mathematica : Fasciculation of cDRG neurite extensions was assessed through a radial tangent vector profile analysis program 79. Briefly, tangent lines were fit to continuous lines of fluorescence in immunofluorescent images of cDRG extension at day 4 of culture.…”
Section: Methodsmentioning
confidence: 99%
“…The development of a disentanglement-focused model will enable users to analyze images featuring multiple neurons, even without 'rainbow' stains like BrainBow or TetBow 21 . This approach would effectively address the limitations inherent in many current methodologies [22][23][24][25] . With the expansive potential of a CNN-based classification system, we can harness is to advance the field of biomedical image analysis and examine individual cells in detail in a high throughput manner.…”
Section: Discussionmentioning
confidence: 99%
“…Each classifier was generated using "neural architecture search", by randomizing various parameters and then inferring on additional images. The following parameters were randomly assigned: CNN kernel size (2)(3)(4), CNN initial number of filters (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), CNN depth (max(1, log(image width, kernel size))), and filter increase rate (1.25 to 1.75). The number of dense layers after convolution starts with a random size that is no more than half of the flattened size.…”
Section: Machine Learning Trainingmentioning
confidence: 99%
“…At 1 or 2 days after seeding, cultures were incubated with a fluorescent vital dye (5carboxyfluorescein diacetate, acetoxymethyl ester; Molecular Probes, Invitrogen) according to our previous protocols from 2D culture studies (Martínez et al, 2016;Richeri et al, 2010) Neurite fasciculation. Manual quantitative analysis of bundles of neurites was done with ImageJ software using the segmented line tool, according to published protocols (Hopkins et al, 2014). 16 neurites per image were selected randomly.…”
Section: Microscopy Imaging and Quantitative Assessment Of Neuritementioning
confidence: 99%